Analysis of radiation patterns of compound box-horn antenna - Gupta, R.C.; Singh, S.P. (My University, 2007)
A new type of antenna named as compound box-horn antenna is designed and analyzed for its radiation pattern. The present analysis is based on plane wave spectra for three-dimensional fields. The compound box-horn antenna is obtained by combining modified box-horn and pyramidal horn antennas, in which modified box-horn is coupled to pyramidal horn to excite TE10- and TE 30- modes at the input of pyramidal horn. Thus, the compound box-horn antenna has properties and advantages of both the modified box-horn and pyramidal horn antennas. The radiation patterns and corresponding half-power beam widths (HPBWs) of compound boxhorn antenna in free-space are computed at 10 GHz and compared for different flare angles in E- and H-planes of larger size pyramidal horn section of the compound box-horn. The results for HPBWs in Eand H-planes demonstrate that the radiation patterns in E- and H-planes for compound box-horn can be made narrower by decreasing the flare angles in both E- and H-planes of larger size pyramidal horn section of the compound box-horn. The radiation patterns of compound box-horn are also compared with those for TEio-mode pyramidal horn of same aperture size and it found that the former horn is narrower in E- as well as H-plane than the latter. The analysis has been validated against the experimental results available in the literature. The work presented here can provide useful design guidelines for development of prototypes of compound box-horn which may find potential application as a high-directivity transmitting horn for antenna measurements in the laboratory or as a range illuminator, or in microwave communication etc.
Keywords: Directional patterns (antenna); Electromagnetic wave transmission; Microwaves; Natural frequencies